2022
DOI: 10.1371/journal.pone.0277942
|View full text |Cite
|
Sign up to set email alerts
|

The cytological and electrophysiological effects of silver nanoparticles on neuron-like PC12 cells

Abstract: The aim of this study was to investigate the toxic effects and mechanism of silver nanoparticles (SNPs) on the cytological and electrophysiological properties of rat adrenal pheochromocytoma (PC12) cells. Different concentrations of SNPs (20 nm) were prepared, and the effects of different application durations on the cell viability and electrical excitability of PC12 quasi-neuronal networks were investigated. The effects of 200 μM SNPs on the neurite length, cell membrane potential (CMP) difference, intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…These results suggested that Z-LIG induced mitochondrial division and affected the mitochondrial dynamic in HL-60 cells. The severe energy impairment resulting from the inactivation of mitochondrial ATP synthase is an early event in cell death [ 42 , 43 ]. This was also demonstrated in the present study, where Z-LIG significantly reduced mitochondrial ATP levels in HL-60 cells at 5 µM and significantly inhibited cell survival at 10 µM.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that Z-LIG induced mitochondrial division and affected the mitochondrial dynamic in HL-60 cells. The severe energy impairment resulting from the inactivation of mitochondrial ATP synthase is an early event in cell death [ 42 , 43 ]. This was also demonstrated in the present study, where Z-LIG significantly reduced mitochondrial ATP levels in HL-60 cells at 5 µM and significantly inhibited cell survival at 10 µM.…”
Section: Discussionmentioning
confidence: 99%